Leading Change in Legal Education: Interesting Ideas for Interesting Times - Penelope Watson (Legal Education Review)
Law is a text-based discipline. The comprehension and interpretation of the written word lies at the core of legal reasoning and underpins legal writing. This article argues that developing the skills of critical legal reading is fundamental to all aspects of legal education and ultimately, to the practice of law. Law teachers have mastered and internalised the processes of legal reading, and sometimes therefore overlook the need to teach them explicitly to law students, who are novices. This paper examines the necessary mechanics, techniques and dispositions of critical legal reading in an overall taxonomy, contending that teaching these aspects in explicit and concrete ways is essential for students who are acquiring legal reading skills. Drawing on education, psychology and linguistic research fields, we offer a contemporary account of critical legal reading as a teachable skill and a core component of the undergraduate curriculum in law.